cultural input markets in India – Recent policy reforms and way forward: A review - Padmaja, Subash Surendran; J, Balaji S; Pal, Suresh (The Indian Journal of Agricultural Sciences, 2020)
The paper reviews the policies in three major input sectors; seeds, pesticides and fertilisers. There are many new policies (regulations and acts) which are recently implemented, few recommended and few others yet to be implemented. The new policies and regulations are tailored for the changing dynamics in the input sector and are intended to have greater implications on restructuring the sector. The input sectors are governed by different actors and roles. The current challenges in the agri-input markets are lack of quality seeds and emerging technology policy conundrums in seed sector, lower innovation and research and development in pesticide sector, and subsidy governance in fertilizer sector. We have discussed how these challenges are being addressed by the new policies and what is the plausible way forward.